Medical Expertise at Yekaterinburg Hospital: Legislation and Practice in 1720s–1750s - A. Plate (Научный диалог, 2025)
This article examines the process of conducting medical expertise at the Yekaterinburg Hospital during the years 1720 to 1750. It highlights that medical examination was mandated by legislation in cases of early resignation from factory service due to health issues, constituting one of the primary responsibilities of the medical institution. The objective of this study is to reconstruct the administrative and medical procedures that had developed within the mining administration by the end of the 1720s. The main source base consists of documentary evidence from official records, with significant emphasis on excerpts from medical histories, as well as originals and copies of passports dated between 1747 and 1751, issued to skilled and laboring individuals by the Office of the Chief Factories Administration due to loss of work capacity. The article analyzes the processes and practices surrounding medical examinations at the Yekaterinburg Hospital. It reveals the most common illnesses and occupational injuries among factory workers that prompted requests for medical assistance. Criteria for assigning temporary or permanent disability are identified. The study concludes that the healthcare system in the mining sector exhibited a distinctly military character. It demonstrates that, in accordance with existing legislation, the management of the Yekaterinburg Hospital was obligated to consider not only the principles of medical ethics but also the needs of the treasury for human resources.